Collision coupling in the GABAB receptor–G protein–GIRK signaling cascade. Issue 18 (21st August 2017) - Kahanovitch, Uri; Berlin, Shai; Dascal, Nathan
Abstract : The signaling cascade comprising the 4‐aminobutyrate(B) receptor (GABAB R), G protein and the G protein‐gated K + channel (GIRK) mediates neuronal inhibition in the brain. Precoupling between components of the pathway (within a permanent macromolecular complex) has been proposed, but this remains debatable. We investigated this mechanism in Xenopus oocytes by varying the expression of the GABAB R. Increased expression of GABAB R accelerates activation of GIRK by agonist, implying that some of the components in this cascade interact by a classical collision mechanism. We also find that GABAB R has a bidirectional effect on the basal activity of the GIRK channel. Our results suggest a complex mechanism of coupling between GABAB R and GIRK which involves elements of both precoupling and collision coupling. Abstract :